A Theory towards a Built-in-Variety in Museum Design: The "Capriccio Museum" - Batakoja, Meri (University of Zagreb, Faculty of Architecture, 2023)
The paper presents an excerpt from the extensive research on various museal spaces throughout human history. By re-evaluating the imaginative procedures involved in conceiving those spaces, the research in its broadest scope asks: how do we map, rethink and revive the historically valuable assets of architectural thought without “museumising” them? The excerpt is initially dedicated to the neoclassical museum space based upon the notion of the frame that was already adopted by the painting genre capriccio to induce the spectator’s mind into an architectural fantasy of juxtaposed real and fictitious buildings, archaeological ruins, urban and natural landscapes. In the neoclassical museum space, the capriccio “became alive” as an actual-size architectural fantasy that could be stepped into. Based upon multiple conceptual frames, the interconnected yet distinct architectural fragments illustrated the neoclassical worldview founded on inclusivity, synchronicity and bodily experience. This historical episode is further theorised into the capriccio museum, a new theoretical model that critically perceives multiple experience probabilities as distilled from the past and starts a process of conversion of that historical knowledge into transhistorical knowledge relevant for today.
Keywords: Capriccio, neoclassical, museal spaces, museum typology, transhistorical